Complicaciones postquirúrgicas en pacientes sometidos a colecistectomía laparoscópica en el Hospital Isidro Ayora, Loja - Cabrera González, Diana Patricia (2023)
Laparoscopic cholecystectomy is the first choice treatment in non-malignant diseases of the gallbladder. Although it is a safe surgical procedure, it is not exempt from presenting difficulties. The general objective of this research was to determine the postsurgical complications that occur in patients undergoing laparoscopic cholecystectomy at the Isidro Ayora Hospital, Loja, the specific objectives were: to determine which complications occur most frequently after laparoscopic cholecystectomy, to know factors related to complications after surgery, to determine which of the complications has the greatest relationship to morbidity and mortality in patients. A descriptive, retrospective and quantitative design was used, with patients who underwent laparoscopic cholecystectomy from 2020 - 2021. We worked with a universe of 700 patients, using inclusion criteria. The most frequent complication after a laparoscopic cholecystectomy was bleeding with 40%, while, in the risk factors, the comorbidity that stood out the most is obesity with 4.21%. Complications after laparoscopic cholecystectomy (bleeding) were in the highest percentage, distributed in the age between 20 to 30 years, which represents 2.50%, from 31 to 40 years, 2.35%, as for the female sex, it represents 2. .46%, with a lower incidence for men with 1.69%. In the last objective, after an analysis, some complications are determined that could involve the risk of people's lives, however, there was no person who died, therefore, the result is 0% morbidity and mortality